Konsep diri dan motivasi melanjutkan pendidikan ke perguruan tinggi pada remaja panti asuhan “x” - Tanri Fatma Utami; Rahmah Saniatuzzulfa (Cognicia, 2021)
The low number of high school graduates in Purworejo who continue their education to college is caused by the students’ concerns about the high cost of education and lack of student confidence in their abilities. One of those who experienced this was an orphanage teenager. Teenagers in orphanages are teenagers who are deliberately entrusted by their parents to get a decent life and education. This study aims to determine the relationship between self-concept and motivation to continue education to college. The sample recruitment was determined using cluster random sampling method and found 81 teenage orphanages as participants. The instruments used are the Motivation Scale Continuing Education to Higher Education with 43 (a = 0.930) and the Self Concept Scale with 25 (a = 0.870). The results of a simple regression analysis showed that there is a significant positive relationship between self-concept and motivation to continue education to college (F = 105.700; p < 0.05; r = 0.756). SE contributed 57,632% of the motivation to continue their education to college.   Keywords: Motivation to continue study to the college, orphanage teenager, self-concept